Utopía y estética feminista descolonial: diálogos imaginarios con Aníbal Quijano para la revolución de nuestro tiempo - Bidaseca, Karina (2019)
The question about utopia and aesthetics opens up an unexplored territory of the legacy of Anibal Quijano in our contemporary world. This text addresses, from a descolonial feminist perspective, the aesthetic possibilities that the notion of utopia, inaugurated by the Peruvian sociologist, opens within the framework of the debates on the theory of the coloniality of power and gender. This essay seeks to explore the aesthetic sense of utopia in the search for another society that, necessarily today faces a world in which the veils have been run. Before our astonished eyes, we observe the dangerous order of domination of the fundamentalisms, with the most perverse visions of the occidentalism and ideology of gender associated with the forms of cultural imperialism, whose script is indelibly written in the bodies of women and dissidents. How to de-learn from the universe of concepts typical of Western philosophy and aesthetics towards a situated thinking? How to decolonize the Western aesthetic imaginary and how to dismantle the racist and sexist imaginaries of the modern / colonial order? How does your perspective help us to identify feminist and sexual dissidence experiences of aesthetic and utopian subversion today?